Vancomycin concentrations during cardiopulmonary bypass in pediatric cardiac surgery: a prospective study. (September 2022) - Ferrari, Fiorenza; Benegni, Simona; Marinari, Eleonora; Haiberger, Roberta; Garisto, Cristiana; Rizza, Alessandra; Giorni, Chiara; Quattrone, Maria Giovanna; Arpicco, Silvia; Muntoni, Elisabetta; Milla, Paola; Ricci, Zaccaria
Introduction: Few data are available regarding intraoperative plasma concentrations of vancomycin administered as prophylaxis in pediatric cardiac surgery. The aims of this study were to investigate during pediatric cardiac surgery with cardiopulmonary bypass(CPB) the attainment of the area-under-the-curve of the vancomycin serum concentrations versus time over surgery to minimum inhibitory concentration ratio(AUCintra /MIC) of 400 (mg × h)/l and/or a target concentration of 15–20 mg/l. Methods: In a prospective study, 40 patients divided into four subgroups (neonates, infants, children <10 years-old, ⩾10 years-old) undergoing cardiac surgery with cardiopulmonary bypass (CPB) were enrolled. A slow vancomycin bolus of 20 mg/kg, up to a maximum dose of 1000 mg was administered before skin incision and a further dose of 10 mg/kg (up to 500 mg) at CPB start. Vancomycin samples were collected intraoperatively at four time points. Results: The median (interquartile range) age was 241.5 days (47–3898) and the median weight was 7.1 kg (3.1–37). The median AUCintra /MIC was 254.73 (165.89–508.06). In 11 patients the AUCintra /MIC target was not reached. Neonates displayed the lowest AUCintra /MIC values, and these were significantly lower than those of children ⩾10 years old (p = 0.02). Vancomycin concentrations were above the maximal target of 20 mg/l in 82.5% and 80% of patients at surgery and CPB start, respectively. At CPB and surgery end, 42.5% of patients showed vancomycin concentrations above 20 mg/l and 42.5% below 15 mg/l. Patients⩾10 years old showed the highest peak values whereas neonates were those with the lowest troughs. AUCintra /MIC correlated with age(r:0.36, p = 0.02), weight(r:0.35, p = 0.03), intraoperative protein value(r:0.40, p = 0.01), CPB priming volume/kg(r:−0.33, p = 0.04), CPB duration(r:0.36, p = 0.02) and vancomycin troughs(r:0.35, p = 0.04). Conclusions: An AUCintra /MIC ⩾400 target was not reached in one-quarter of children undergoing heart surgery. Vancomycin peaked before the start of surgery and neonates were those with the lowest troughs. Vancomycin concentrations are affected by CPB hemodilution and by patients' age and weight.